Growth in emerging market economies and the commodity boom of 2003 - 2008: Evidence from growth forecast revisions - Elif C. Arbatli; Garima Vasishtha (Bank of Canada, 2012)
Demand for industrial raw materials from emerging economies, particularly emerging Asia, is widely believed to have fueled the surge in oil and industrial commodity prices during 2002-2008. The paper first presents a simple storage model in which commodity prices respond to market participant's changing expectations of the future macroeconomic environment. In the model, the change in the price of a commodity depends on the unanticipated changes in demand factors, along with the real exchange rate, the real interest rate, and other factors that affect the marginal convenience yield. It then focuses on the role of demand factors by using a newly constructed monthly measure of unanticipated demand shocks for commodities based on revisions to professional forecasts of industrial production growth for a large group of emerging market and advanced economies. The empirical framework also controls for other macroeconomic factors that affect commodity prices, such as the real effective exchange rate (REER) of the U.S. dollar and the real interest rate. The results show that revisions to growth forecasts for emerging Asia play an important role in explaining movements in the real prices of industrial metals. In addition, the REER of the U.S. dollar is an important determinant of industrial commodity prices. For crude oil, growth forecast revisions for the U.S. and the real interest rate play a significant role in explaining real prices. Furthermore, growth surprises in general fall short of explaining the fast run-up in most commodity prices during 2006-2008, and the magnitude of the collapse in prices during the recent global financial crisis.
Keywords: Q41; Q43; 330; Econometric and statistical methods; International topics